Antimicrobial stewardship: from theory to reality in a resource-limited setting (and beyond) - Ochoa-Hein, Eric; Galindo-Fraga, Arturo (Frontiers in Antibiotics, 2024)
Correct use of antibiotics is paramount to present global health. Among other actions, antimicrobial stewardship emphasizes de-escalation and suspension whenever possible. Nonetheless, roadblocks can be encountered (e.g., lack of culture results or availability of specific antibiotic classes). Furthermore, in an everincreasing interconnected world, global success relies on local success. In this perspective, a particular case study in a resource-limited setting is an example of the many difficulties encountered in the fight against antimicrobial resistance that could hamper global advancements.